Criterion for Imminent Failure During Loading—Discrete Element Method Analysis - Dȩbski, Wojciech; Pradhan, Srutarshi; Hansen, Alex (Frontiers in Physics, 2021)
It has recently been reported that the equal load sharing fiber bundle model predicts the rate of change of the elastic energy stored in the bundle reaches its maximum before catastrophic failure occurs, making it a possible predictor for imminent collapse. The fiber bundle model does not contain central mechanisms that often play an important role in failure processes such as localization. Thus, there is an obvious question whether a similar phenomenon is observed in more realistic systems. We address this question using the discrete element method to simulate breaking of a thin tissue subjected to a stretching load. Our simulations confirm that for a class of virtual materials which respond to stretching with a well-pronounced peak in force, its derivative and elastic energy we always observe an existence of the maximum of the elastic energy change rate prior to maximum loading force. Moreover, we find that that amount of energy released at failure is related to the maximum of the elastic energy absorption rate.